Analisis Faktor-Faktor Mempengaruhi Indeks Pembangunan Manusia di Provinsi Sumatera Bagian Selatan - Resilia Salsabila; Muhammad Husaini (Departement of Mathematics Education, 2023)
The primary objective of this research is to assess the relationship between poverty and public education expenditure on the human development index in the province of Southern Sumatra. Ordinary Least Squares analysis (OLS) is used in this probe. The data used in this study includes secondary data gathered in five southern Sumatra provinces between 2016 and 2021. Poverty has a negative and considerable impact on human development in the Province of Southern Sumatra, whereas state investment in the education sector has both a good and negative impact. crucial for Southern Sumatra's Provincial Human Development Index, everything else being equal. Poverty and government spending on education have major effects on the human development index in the southern Sumatra province.